A congestion control algorithm for the deep space Internet - Luigi Grieco; Saverio Mascolo (Space Comms., 2005)
This paper proposes a new rate based congestion control algorithm that significantly improves the utilization of planetary links with respect to classic TCP congestion control. Ns-2 simulation results have shown that the proposed algorithm provides significant goodput improvements with respect to New Reno, Reno Sack, Reno Fack, Vegas, and Westwood+ TCP in the presence of RTTs larger than 1 s and smaller than 2000 s and packet loss probability ranging from 0.0001 to 0.01.
Keywords: Congestion control; TCP; Planetary Internet